If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(q + 2) = 8 Reorder the terms: 2(2 + q) = 8 (2 * 2 + q * 2) = 8 (4 + 2q) = 8 Solving 4 + 2q = 8 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2q = 8 + -4 Combine like terms: 4 + -4 = 0 0 + 2q = 8 + -4 2q = 8 + -4 Combine like terms: 8 + -4 = 4 2q = 4 Divide each side by '2'. q = 2 Simplifying q = 2
| 3/4=Y/7 | | 1080*x=917 | | 1080-x=163 | | -24=-12w | | -7=3v+2 | | 24=-w/6 | | 4z/7-5=-2 | | 144+12c=300 | | 2*2*2+-3*-3= | | 1080*x=955 | | -u/6=-42 | | 20=2+3u | | (7x^4)/(sqrt(2x-8)) | | 2.3log(x)=3log(6-x) | | 6x+y+z=10 | | -4u+5=5-4u | | 1920*x=5 | | -15=4u-3 | | 4lnx-1=6 | | 5/4=7x^2-x | | 42+x=(13+x)*2 | | 21y+7=5 | | 5/2*32 | | Y=-xy-3x-3 | | 11=2/3x-3 | | 2y=5y-8 | | 1920*x=2 | | x-(0.75x+1)=1 | | 4=4xW | | 4x^3+18x=0 | | 7-3-2/5v | | 3x-(x+1)=9 |